1973
DOI: 10.1111/j.1151-2916.1973.tb12718.x
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectrum of PbZrO3

Abstract: Laser-induced Raman spectra were obtained for powders and multidomain single crystals of PbZrO, at room temperature. Factor-group analysis was used to interpret the spectra on the basis of the space group CZos-Pba2. Raman spectra were also observed for single crystals of PbZrO, at several other temperatures between 76" and 520°K and related to crystal structural changes. No first-order Raman bands were noted above the Curie temperature, indicating a phase transformation to a cubic zirconate structure. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 9 publications
5
31
0
Order By: Relevance
“…52 A single low frequency peak positioned at 80 cm −1 of antiferroelectric origin was also observed in the antiferroelectric perovskite Sr 0.70 Ca 0.30 TiO 3 . 55 Consistent with these related compounds, we assign the 60 cm −1 mode in Bi 0.8 La 0.2 FeO 3 to an antiferroelectric displacement of the A site.…”
Section: The La20 Structurementioning
confidence: 91%
“…52 A single low frequency peak positioned at 80 cm −1 of antiferroelectric origin was also observed in the antiferroelectric perovskite Sr 0.70 Ca 0.30 TiO 3 . 55 Consistent with these related compounds, we assign the 60 cm −1 mode in Bi 0.8 La 0.2 FeO 3 to an antiferroelectric displacement of the A site.…”
Section: The La20 Structurementioning
confidence: 91%
“…For the Raman-based stress analysis, the mode located at ∼415 cm −1 in stress-free bulk PZO was selected, and the amount of stress was calculated from the shift of the peak with change in d PZO . 34,35 RT polarization characteristics of the heterostructures were investigated by measuring their macroscopic dynamic P-E and static P-E hysteresis responses 36 using an AixAcct TF analyzer 2000 (aixACCT Systems GmbH). In case of the dynamic P-E hysteresis measurements, the nonzero leakage current at small applied voltages adds a parasitic contribution to the integrated charge, which might yield a spurious value of the in-field P r .…”
Section: Methodsmentioning
confidence: 99%
“…Based on single-crystal work, the bands at 204 and 232 cm 1 bonding, the bands at 285, 330 and 344 cm 1 have been assigned to ZrO 3 torsions and those at 501 and 532 cm 1 are due to Zr-O stretching. 69 The temperature evolution of the Raman spectra for PZ films suggested that annealing above 898 K results in orthorhombic PZ. 70 The existence of two phase transitions and the intermediate ferroelectric phase between the anti-ferroelectric and paraelectric phases in PZ was evidenced by x-ray diffraction and neutron scattering investigations.…”
Section: B-site Substitution In Pbtiomentioning
confidence: 99%